2019
DOI: 10.1080/02656736.2019.1685685
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between the changes of skin temperature and radiation skin injury

Abstract: Background: Radiation skin injury (RSI) causes changes in skin temperature, but detailed information on the thermographic responses is currently lacking. We investigated thermographic patterns after radiotherapy. We hypothesized that skin temperature may be used as a diagnostic and early predictor of RSI severity. Method: All breast cancer patients received radiotherapy after unilateral postmastectomy. The contralateral supraclavicular area served as control, and the frontal thermal image of torso was taken by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 24 publications
2
11
2
Order By: Relevance
“…Interestingly, a recent study by Zhu et al demonstrated that in comparison to the baseline, the difference of average and maximum skin temperature increased significantly over time during radiotherapy ( p <.05). The onset of this increase was accompanied by radiation dermatitis, and the maximal temperature change also appeared at the peak of Radiation Therapy Oncology Group (RTOG) scores 30 . All the factors mentioned above may have their specific role in the culmination of our patient's home remedy with opioid overdose symptoms and emergency admission.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Interestingly, a recent study by Zhu et al demonstrated that in comparison to the baseline, the difference of average and maximum skin temperature increased significantly over time during radiotherapy ( p <.05). The onset of this increase was accompanied by radiation dermatitis, and the maximal temperature change also appeared at the peak of Radiation Therapy Oncology Group (RTOG) scores 30 . All the factors mentioned above may have their specific role in the culmination of our patient's home remedy with opioid overdose symptoms and emergency admission.…”
Section: Discussionmentioning
confidence: 90%
“…The onset of this increase was accompanied by radiation dermatitis, and the maximal temperature change also appeared at the peak of Radiation Therapy Oncology Group (RTOG) scores. 30 All the factors mentioned above may have their specific role in the culmination of our patient's home remedy with opioid overdose symptoms and emergency admission. Furthermore, the existing moist environment (tissue hydration) and the occlusive nature of the latex residue applied on the skin possibly contributed further to both systemic absorption and skin infection.…”
Section: Discussionmentioning
confidence: 99%
“…The trend of the reduced the temperature at 6 months after RT was observed, which may relate to the healing process. The general recovery of irradiated tissue will probably lead to temperature equalization over the long-term follow-up period [ 45 ]. However, late radiation effects may change the local microenvironment and tissue metabolism owing to persistent subtle differences in temperature.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer cells that divide rapidly are more susceptible to ionizing radiation-they are said to be radiosensitive. Based on the available literature on the effects of radiotherapy on the body, as well as on the knowledge of the effects of radiation over time, it has been assumed that radiotherapy can cause changes in the body temperature that we can observe with thermovision [50][51][52][53].…”
Section: Discussionmentioning
confidence: 99%